Prospects for the introduction of artificial intelligence into the accounting information generation system ("Journal "U". Economy. Management. Finance.", 2025)
The article reveals the functionality of introducing artificial intelligence into an accounting system as an element of a corporate information system. The technological priorities of the introduction of artificial intelligence in the financial sector of corporations and government agencies are highlighted. The categories of accounting processes that AI technologies are aimed at digitizing are presented. The author highlights the complicating factors of the introduction of artificial intelligence into the management information formation system, the elimination of which is ensured by the implementation of a set of developed measures. In terms of the accounting system, the emphasis is on the accuracy and speed of data acquisition, as well as compliance with regulatory requirements.
Keywords: artificial intelligence; digitalization of accounting; corporate information system; accounting; accounting information